O papel do preceptor no processo formativo dos residentes de Educação Física do programa residência pedagógica em Parintins, Amazonas - Silva, Matheus Fernando Pereira e (2024)
The theme of this study aims to investigate the perception of preceptors about the Pedagogical Residency Program (PRP), identifying the effects of this practice on teacher training. The study has a qualitative and descriptive approach, using as an instrument a semi-structured interview, a sheet of notes, a cell phone audio recorder and an audio transcription application Transkriptor. Participants in this research were three teachers from public schools in the state education network, who act as preceptors of the Physical Education subproject of the Pedagogical Residency Program. Data analysis was based on Bardin's Content Analysis (1977). The study demonstrates that the preceptor highlights the importance of the PRP in the performance and construction of the resident's teaching identity. Through the interviews, it was possible to analyze that the main contributions of the preceptors to the residents were the construction of self-confidence, the ability to deal with the public and autonomy, experiencing what it is like to be a teacher. The preceptors is the main link in the program that encourages the resident to put into practice the knowledge acquired at the University, providing them with experiences that go beyond school boundaries.